REGIONAL LOGISTICS CENTER: FORMATION AND FUNCTIONING SPESIFIC - Tkach, O.V.; Voloshchuk , I.A. (The actual problems of regional economy development, 2017)
In this article the essence of the definition of logistics centers is defined, the main provisions concerning the formation of the logistics center are defined. The formation of a logistic hub is analyzed. The structure of the transport-logistic center is proposed. The basic requirements for the location of the regional logistics center and the principles of its operation are determined. The financial and financial mechanism of a typical logistics center and their effective functioning are presented. It is proved that the most important component of the logistics center is transport.